Um estudo de acompanhamento da vivência da dança do ventre como recurso terapêutico com mulheres mastectomizadas - Silva, Rafaella Brito e (2015)
This thesis, which is the result of a personal and professional experience with dancing, as well as of an interest in studies and initiatives in the field of Psycho-oncology, consisted of a follow-up research study based on the theoretical framework of Gestalt Therapy. The aim of the study was to investigate how mastectomized women who underwent a group corporeal intervention, with belly dancing as a therapeutic means, perceived themselves in their corporeality three years after their experience. The importance of this study is related to the need to expand therapeutic strategies for health promotion during the breast cancer post-treatment of mastectomized women. It comprises a qualitative survey in which follow-up interviews were conducted in groups and individually. The analysis and discussion were based on the collaborators' reports, by employing the phenomenological method. It was possible to identify that belly dancing played an important role in copying with the disease and also in the participants' lives. Belly dancing helped to mobilize resources in order to deal with the changes resulting from the treatment, as well as changes in the maturing process. The dance, the music and the movement were perceptible as a trigger for the promotion of contact with femininity and sensuality in a pleasant and ludic way. The therapeutic group was significantly important as an outer support, providing a welcoming space for experiencing the body and for the exchange of experiences. It can be concluded that belly dancing is a potential therapeutic tool in the rehabilitation of mastectomized women in the long term too